Impact of economic crisis on life span and its spatial inequalities in Hungary - Uzzoli, Annamária (Discussion Papers, 2022)
The credit crisis in Autumn 2008, the deepening world economic crisis in 2009, and the crisis of the Euro emerging in 2010 raise the following question: if the crisis affects the financial and economic processes, would it be instrumental in the functioning of social and health sectors? If the answer is yes, other questions arise, such as: how and in what measure. It is unquestionable that the crisis has been taking effect on the people’s state of health, although the impacts are complex. The crisis, which is perceptible in all sectors of economic life, has directly affected households and their health behaviour connected with health preservation or prevention. The social resources for healthcare and the development of the sector have been exhausted, non-wage based health expenditure has been drastically cut back. Most of the European countries should be prepared for the treatment of the direct and indirect social, health and healthcare consequences of the crisis. Central and Eastern European countries face particularly serious challenges, where already existing healthcare conflicts would re-appear and health inequalities would become more acute due to the recent crisis. In particular, the health status of the Hungarian population has been extremely unfavourable for many decades. Regarding certain diseases and causes of death, Hungary is in a negatively outstanding position in international statistics, and has one of the lowest life expectancy rates at birth among the member states of the European Union. This paper uses statistical analytical methods (correlation and regression calculations) to explain cause-and-effect relationships between unemployment and life chances with. Data is used to describe tendencies, as well as to prove regional and spatial differences. The levels of examination of the statistical analysis are the counties (NUTS3) and micro-regions (LAU1). The significance of the results of the enquiry lies in the regional characteristics of public health processes, and socio-economic factors determining the state of health.